Topical Ganciclovir for Prophylaxis of Cytomegalovirus Endotheliitis in Endothelial Keratoplasty. Issue 1 (January 2019) - Basilious, Alfred; Chew, Hall F.
Abstract : Purpose: To describe the presentation and management of 2 cases of Descemet stripping automated endothelial keratoplasty (DSAEK) with failure secondary to cytomegalovirus (CMV) infection and prophylaxis with topical ganciclovir to prevent repeat failure of Descemet membrane endothelial keratoplasty (DMEK) regrafts. Methods: A retrospective chart review was conducted for 2 patients with DSAEK failure secondary to CMV infection. Results: A 70-year-old immunocompetent man (case 1) and a 53-year-old immunocompromised man (case 2) received DSAEK for presumed pseudophakic bullous keratopathy and endothelial decompensation secondary to recurrent uveitis, respectively. Case 1 had first graft failure at 10 months and case 2 at 21 months with inferior edema and keratic precipitates. Both failed to respond to topical steroid drops, and case 1 had 3 subsequent failed DSAEKs. Anterior chamber paracentesis confirmed CMV DNA. Neither had a clinical response to 6 weeks of oral valganciclovir. They were then administered topical ganciclovir (0.15% ophthalmic gel), and repeat endothelial transplant (DMEK) was performed for both patients. They were again administered topical ganciclovir 4 times daily after surgery because aqueous samples remained positive for CMV. Both remain free of inflammation or failure on topical ganciclovir for 21 months (case 1) and 29 months (case 2) with uncorrected visual acuities of 20/40 and 20/25, respectively. Conclusions: Long-term topical ganciclovir use can prevent recurrence of CMV-associated graft failure even in immunocompromised hosts without side effects of systemic antivirals. DMEK may have advantages over DSEK in eyes with previous CMV infection and in eyes prone to inflammation.